Analyses of Ship A avoiding the influence caused by typhoon “Doksuri” - Zhang, Zenghai; Zhang, Chengbao; Zhang, Hao; Guo, Yiying; Cao, Yuenan; Wu, Guosheng; Dong, Yiwen; Liu, Tao (Frontiers in Marine Science, 2025)
Maritime transport accounts for approximately 80% of international cargo volume; however, it confronts significant threats from typhoons or hurricanes. Existing typhoon-avoidance strategies are often challenged by uncertainties in the forecast of typhoon intensity and trajectory. This study analyzes the case of a bulk carrier navigating from Australia to China during Typhoon “Doksuri” in 2023. Automatic Identification System (AIS) data and high-resolution meteorological datasets were ultilized, along with an improved Dijkstra algorithm, to construct a navigable typhoon-avoidance route map. A time-minimization objective function incorporating a penalty mechanism for violating typhoon safety distances was established. The bulk carrier adopted four sequential avoidance strategies to evade Typhoon “Doksuri”: reducing speed, front-crossing avoidance, stopping and drifting, and resuming sailing under safe conditions. As a result of these adjustments, the Distance of Closest Point of Approach (DCPA) increased from 101 nautical miles to 183 nautical miles. The maximum encountered wind force was reduced from Beaufort scale 11 to 8, and the significant wave height decreased from 9 meters to 6.5 meters. The research indicates that timely and accurate typhoon forecasts, refined weather and ocean condition forecasts, and precise shore-based meteorological routing services are critical factors for ships to avoid typhoons effectively.